The Flow Pattern in Single and Multiple Submerged Channels with Gas Evolution at the Electrodes. (5th April 2012) - Alexiadis, A.; Dudukovic, M. P.; Ramachandran, P.; Cornell, A.; Wanngård, J.; Bokkers, A.
Abstract : We show that the gas-liquid flow pattern in a single gas-evolving electrochemical channel can be remarkably different from the flow pattern in multiple submerged gas-evolving electrochemical channels. This is due to the fact that in a single channel there is a higher accumulation of small bubbles and these can considerably affect the liquid velocity pattern which in turn may affect the performance of a cell. Since experimental work is often carried out in single channels, while industrial applications almost always involve multiple channels, this study provides insight into the factors that affect the flow pattern in each situation and establishes the basis for relating the behavior of single-and multiple-channel devices.